Deficits in general and smoking‐specific response inhibition in the Go/No‐Go task in individuals who smoke: A cross‐sectional analysis. - Motka, Franziska; Kühn, Simone; Wittekind, Charlotte E. (Addiction, 2025)
Background and aims: Previous studies on response inhibition deficits in smoking have often been conducted in small, young, age‐homogeneous samples, without controlling for covariates or testing moderating effects. The primary research question compared response inhibition between a large, age‐diverse smoking sample and non‐smoking controls, and examined whether deficits were exacerbated toward smoking‐related stimuli. By accounting for key covariates and moderators, this study aimed to extend understanding of individual differences in response inhibition deficits in smoking. Design and setting: Cross‐sectional study conducted at a university laboratory in Munich, Germany. Participants: The large (n = 122, 57% female), age‐diverse (Mage = 41.4, range: 21–70 years) smoking group comprised individuals with moderate to severe tobacco dependence participating in a smoking reduction intervention study. Controls comprised n = 69 healthy individuals with no smoking history. Measurements: Primary outcomes were commission error (CE) rates and mean reaction times in Go trials (Go‐RT) in general and smoking‐specific Go/No‐Go tasks (GNGTs). Covariates included age, sex and IQ. Smoking‐related variables were cigarettes per day (CPD), tobacco dependence severity and craving. Findings General GNGT: The smoking group exhibited significantly higher CE rates (P‐value < 0.001, medium effect, BF10 = 9.06) than the control group. Higher craving was associated with faster Go‐RTs (β = −1.487, P‐value = 0.041). Smoking‐specific GNGT: CE rates were significantly higher in the smoking group only when controlling for covariates (β = 1.272, P‐value = 0.040). Higher craving was associated with higher CE rates during smoking‐related trials (β = 0.108, P‐value = 0.010). The smoking group showed significantly faster Go‐RTs in response to smoking‐related compared with neutral stimuli, relative to the control group (β = −3.326, P‐value = 0.027). Preliminary evidence indicated that greater deficits were associated with higher scores in smoking‐related variables, but only in older individuals. Conclusions: Individuals who smoke appear to exhibit response inhibition deficits, although these are not uniform and seem to be exacerbated during higher reported craving or in response to smoking‐related stimuli. Age may moderate the relationship between deficits and smoking‐related variables.